Biomechanical regulation of drug sensitivity in an engineered model of human tumor. (January 2018) - Marturano-Kruik, A.; Villasante, A.; Yaeger, K.; Ambati, S.R.; Chramiec, A.; Raimondi, M.T.; Vunjak-Novakovic, G.
Abstract: Predictive testing of anticancer drugs remains a challenge. Bioengineered systems, designed to mimic key aspects of the human tumor microenvironment, are now improving our understanding of cancer biology and facilitating clinical translation. We show that mechanical signals have major effects on cancer drug sensitivity, using a bioengineered model of human bone sarcoma. Ewing sarcoma (ES) cells were studied within a three-dimensional (3D) matrix in a bioreactor providing mechanical loadings. Mimicking bone-like mechanical signals within the 3D model, we rescued the ERK1/2-RUNX2 signaling pathways leading to drug resistance. By culturing patient-derived tumor cells in the model, we confirmed the effects of mechanical signals on cancer cell survival and drug sensitivity. Analyzing human microarray datasets, we showed that RUNX2 expression is linked to poor survival in ES patients. Mechanical loadings that activated signal transduction pathways promoted drug resistance, stressing the importance of introducing mechanobiological cues into preclinical tumor models for drug screening.